Therapeutic Effects of All Trans-retinoitc Acid Combined with Transarterial Chemoembolization on Walker-256 Hepatoma in Rats - 方建林 郑传胜 陶红芳 赵辉 任建庄 冯敢生 (Journal of Huazhong University of Science and Technology. Medical sciences, 2010)
In order to investigate the inhibitory effects of all trans-retinoitc acid(ATRA)on differentiation and apoptosis of Walker-256 hepatocellular carcinoma cells and the therapeutic effects of ATRA combined with transarterial chemoembolization(TACE)on rat Walker-256 transplanted hepatocarcinoma,Walker-256 hepatocarcinoma cell lines were treated with ATRA at different concentrations.After culture for 48h,the inhibitory rate of cell proliferation was determined by MTT assay;the changes of Fas and Bcl-2mRNA expres...